The Brain Targeted Drug Delivery System - Bire, Priyanka A.; Sonaye, Harsha V.; Doifode, C.A.; Khekare, Preetesh C. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2017)
The brain is a delicate organ, and nature has very efficiently protected it. The drug accessibility to the central nervous system (CNS) is limited by the blood brain barrier (BBB). Various brain disorders are Parkinson, Alzheimer, Meningitis, Brain abscess, Epilepsy, Multiple sclerosis, Late-stage neurological trypanosomiasis (Sleeping sickness) etc. The management of brain related diseases with the present available therapeutic system is very difficult, as insufficient amount of drug reaches to the brain, due to highly lipophilic nature of blood-brain barrier (BBB). Drug delivery to the brain requires advances in drug delivery technologies. Due to the presence of the blood brain barrier only small lipid soluble drug in the circulation are delivered to the brain cells. Therefore, practical strategies are required for mediating the drug transport across blood brain barrier.